2009
DOI: 10.1142/s0217751x09047673
|View full text |Cite
|
Sign up to set email alerts
|

Modified Perturbation Theory for Pair Production and Decay of Fundamental Unstable Particles

Abstract: We construct an asymptotic expansion in powers of the coupling constant directly of the cross-section for pair production and decay of fundamental unstable particles. The resonant and kinematic singularities arising in the expansion we treat in the sense of distributions. This mode allows us to transform formally divergent integrals into absolutely convergent ones with keeping the asymptotic property of the expansion. The appropriate procedure is elaborated up to an arbitrary order of the expansion. The peculi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…p j ) , (39) where PV denotes the principal value (understood as a distribution, see Ref. 113 ). It would be convenient to define POs through a factorisation of the process into sub-processes, e.g.…”
Section: Lhc Pseudo-observablesmentioning
confidence: 99%
“…p j ) , (39) where PV denotes the principal value (understood as a distribution, see Ref. 113 ). It would be convenient to define POs through a factorisation of the process into sub-processes, e.g.…”
Section: Lhc Pseudo-observablesmentioning
confidence: 99%
“…Furthermore, the MPE should be understood as an "asymptotic expansion", see Refs. [71,72], not as a narrow-width approximation (NWA). The phase space decomposition is obtained by using the two parts in the propagator expansion of Eq.…”
Section: The Strategy: From the Multi-pole Expansion To Pseudo-observmentioning
confidence: 99%
“…The second remark concerns the single-resonant and interference contributions. Actually this issue was discussed earlier [10], and it was shown that such contributions may be taken into consideration precisely by the same technique as discussed above. So in these cases our results about the precision of the MPTdescription must be in force, as well.…”
Section: Discussionmentioning
confidence: 87%
“…For this reason we do not discuss C ν n 1 ,n 2 below.) In the original work [10] the basic integrals were calculated at non-integer ν, and only half-integer ν was needed in the final stage with smooth Φ. At the same time, a transition to integer ν was not obvious because of singular behavior of some factors.…”
Section: Mpt For Angular Distributionmentioning
confidence: 99%